New OTRA-Based Generalized Impedance Simulator. (9th May 2013) - Gupta, Ashish; Senani, Raj; Bhaskar, D. R.; Singh, A. K.
Abstract : Operational transresistance amplifier (OTRA) has attracted considerable attention in the recent literature in several applications such as impedance simulation, universal biquad filter realization, realization of sinusoidal oscillators and multivibrators. However, to the best knowledge of the authors, any OTRA-based generalized impedance simulator circuits have not been reported so far. The purpose of this paper is to present such a circuit.